(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the multifaceted legacy of the Timurid dynasty, particularly under the leadership of Amir Timur (Tamerlane), during the 14th and 15th centuries in Central Asia. It delves into Timur’s rise to power, characterized by ambitious military campaigns that expanded his empire across vast regions. Despite the conquests’ destructive nature, Timur’s reign also witnessed a flourishing of arts and culture, exemplified by the architectural marvels of Samarkand and the intellectual achievements of Timurid scholars. The Timurids’ patronage of art, literature, and scholarship fostered a rich cultural renaissance, with profound influences on Persian and Central Asian traditions. The article explores how Timur’s successors, particularly in Herat and Persia, sustained and further developed this cultural legacy, shaping the artistic landscape of the region for generations. The decline of the Timurid dynasty in the 16th century did not diminish its enduring impact on the Islamic world, evidenced by the continued admiration for Timurid art and architecture today. Through an examination of historical narratives, architectural feats, and artistic achievements, this article illuminates the complex interplay between conquest and cultural innovation during the Timurid era. The enduring legacy of the Timurids underscores their pivotal role in shaping the identity of Central Asia and beyond, leaving an indelible imprint on the artistic, intellectual, and architectural heritage of the regions they once ruled